2012
DOI: 10.1111/j.1399-5618.2012.01000.x
|View full text |Cite
|
Sign up to set email alerts
|

Grey matter differences in bipolar disorder: a meta‐analysis of voxel‐based morphometry studies

Abstract: Bipolar disorder is consistently associated with reductions in right prefrontal and temporal lobe grey matter. Reductions elsewhere may be obscured by clinical and methodological heterogeneity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
150
1
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(183 citation statements)
references
References 62 publications
16
150
1
11
Order By: Relevance
“…This finding goes against those of other VBM studies of patients with bipolar disorder, meta‐analyses of which have found the anterior cingulate cortex, the insula, and the inferior frontal cortex to show volume reductions, among other areas 22, 39, 40. The likeliest explanation of our failure to detect differences is the use of a restrictive threshold of at a P  = 0.01 corrected.…”
Section: Discussioncontrasting
confidence: 78%
“…This finding goes against those of other VBM studies of patients with bipolar disorder, meta‐analyses of which have found the anterior cingulate cortex, the insula, and the inferior frontal cortex to show volume reductions, among other areas 22, 39, 40. The likeliest explanation of our failure to detect differences is the use of a restrictive threshold of at a P  = 0.01 corrected.…”
Section: Discussioncontrasting
confidence: 78%
“…[21][22][23][24][25] Other studies suggest that structural brain changes are found mainly in the frontal, temporal, and limbic white matter (WM) regions. [26][27][28][29][30][31] WM abnormalities have been widely detected in subjects with the pathophysiological features of BD, especially with diffusion tensor imaging (DTI) techniques. 29 Diffusion imaging principles are based on measurement of the motion of water molecules within tissues.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of region-based and voxel-based approaches has already been applied to identify the structural abnormalities associated with SCZ and BD (Arnone et al 2009;Ellison-Wright & Bullmore, 2010;Yu et al 2010;Bora et al 2012;Selvaraj et al 2012). Whole-brain voxel-based morphometry (VBM) studies highlighted overlapping areas of grey matter (GM) reduction in SCZ and BD compared with HC, mainly located in bilateral insula and anterior cingulate cortex.…”
mentioning
confidence: 99%